2005
DOI: 10.1113/expphysiol.2005.030296
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in mouse cardiac proteome after in vivo myocardial infarction: permanent ischaemia versus ischaemia–reperfusion

Abstract: Mice are increasingly used to study the early molecular mechanisms inducing injury to the heart following myocardial infarction. To date, two-dimensional gel electrophoresis combined with mass spectrometry has not been applied to identify changes in protein expression in myocardial tissue of mice subjected in vivo to permanent ischaemia (PI) or ischaemia-reperfusion (IR). In the PI group, ischaemia was induced for 210 min by ligation of the left anterior descending coronary artery while in the IR group, ischae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 51 publications
6
30
0
Order By: Relevance
“…Thus, the need for increased Hsp20 expression becomes more important in the pathophysiological setting of heart failure. Indeed, previous studies have shown that the levels of Hsp20 as well as its phosphorylation levels at Ser 16 increase in the diseased myocardium (7,10,12,16,18) as a protective mechanism (7, 13, 14 -17). Consistent with these findings, we observed that the extent of apoptosis was reduced significantly in cells infected with Ad.WT-Hsp20 after simulated I/R compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the need for increased Hsp20 expression becomes more important in the pathophysiological setting of heart failure. Indeed, previous studies have shown that the levels of Hsp20 as well as its phosphorylation levels at Ser 16 increase in the diseased myocardium (7,10,12,16,18) as a protective mechanism (7, 13, 14 -17). Consistent with these findings, we observed that the extent of apoptosis was reduced significantly in cells infected with Ad.WT-Hsp20 after simulated I/R compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…At basal levels, no phosphorylated Hsp20 could be detected, consistent with the low activity of PKA in isolated myocytes. To test the specificity of this antibody, peptide competition was performed with the anti- [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] in human, dog, rat, and mouse shows that proline 20 is fully conserved. B, secondary structure predictions revealed alterations in the helical content around the Ser 16 phosphorylation site as well as around the site of the mutation.…”
Section: Identification Of a Human Hsp20 Mutant (C59t)-to Identify Vamentioning
confidence: 99%
See 1 more Smart Citation
“…Brief ischemia with reperfusion and prolonged ischemia elicit different patterns of protein and gene expression, thereby activating different pathways in the heart (8). In addition, ANP like other molecules (e.g., P-selectin; see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In organs with a weaker repairing ability, such as heart and brain, the ischemic injury rapidly leads to infarction and fibrosis. [6][7][8][9][10][11] On the other hand, the fibroid involution of the renal parenchyma is mainly observed as a result of a chronic ischemic-hypoxic or inflammatory injury. [12] The ability of the kidney to repair the ischemic damage is due to several factors that are still not completely known.…”
Section: Introductionmentioning
confidence: 99%